2021
DOI: 10.1186/s12877-021-02566-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute stroke treatment and outcome in the oldest old (90 years and older) at a tertiary care medical centre in Germany-a retrospective study showing safety and efficacy in this particular patient population

Abstract: Background Stroke is among the most common causes of death and disability worldwide. Despite the relevance of stroke-related disease burden, which is constantly increasing due to the demographic change in industrialized countries with an ageing population and consecutively an increase in age-associated diseases, there is sparse evidence concerning acute stroke treatment and treatment-related outcome in the elderly patient group. This retrospective study aimed at analysing patient characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…This report has documented safety and benefit of EVT in patients who are 90 years and older in a community hospital setting, further supporting EVT in eligible advanced aged patients. Our outcomes were equivalent to, although there are few, other published studies [10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This report has documented safety and benefit of EVT in patients who are 90 years and older in a community hospital setting, further supporting EVT in eligible advanced aged patients. Our outcomes were equivalent to, although there are few, other published studies [10].…”
Section: Discussionsupporting
confidence: 81%
“…The landmark HERMES collaborative trial (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials), and its sub-study suggest not withholding EVT on the basis of age alone [7,8] although surveyed clinicians state that age still plays a key role when making individual thrombectomy decisions [9]. In addition, the most recent guidelines from the American Stroke Association/American Heart Association suggest more studies are needed for patients >=90 years especially in the “real-world setting” [10].…”
Section: Introductionmentioning
confidence: 99%
“…Death rates have been demonstrated to be similar between groups in other studies [ 6 8 , 12 , 13 ], according to randomized evidence [ 2 ]. Our study has several limitations and possible biases.…”
Section: Discussionmentioning
confidence: 67%
“…However, in numerous countries, guidelines tend to view age as a relative exclusion criterion for patients aged 80 and above within the 3–4.5-h treatment window [ 3 – 5 ]. Despite comparable bleeding risk to younger groups and observed higher probabilities of improved functional outcomes compared to non-thrombolyzed patients of the same age, some guidelines continue to emphasize age-related considerations [ 6 8 ]. The aim of this study was to investigate the safety and efficacy of rtPA treatment in previously ambulatory patients aged 90 years or older with moderate or severe AIS admitted to our institution.…”
Section: Introductionmentioning
confidence: 99%
“…[45,46] Another acute stroke treatment and outcomes in the oldest old (90 years and older) at a tertiary care medical center in Germany found that acute stroke treatment is effective and safe in the oldest old. [47] A higher NHISS score was an independent risk factor for stroke recurrence in patients with a history of stroke. [29] Lai et al [48] found that NIHSS can be used as a risk factor for 90-day prognosis in patients undergoing thrombectomy (EVT), and the 7-day NIHSS score is more accurate.…”
Section: Discussionmentioning
confidence: 89%